Reduced steroidogenesis in patients with PCDH19‐female limited epilepsy. (4th May 2017) - Trivisano, Marina; Lucchi, Chiara; Rustichelli, Cecilia; Terracciano, Alessandra; Cusmai, Raffaella; Ubertini, Grazia Maria; Giannone, Germana; Bertini, Enrico Silvio; Vigevano, Federico; Gecz, Jozef; Biagini, Giuseppe; Specchio, Nicola
Summary: Patients affected by protocadherin 19 (PCDH19)–female limited epilepsy (PCDH19‐FE) present a remarkable reduction in allopregnanolone blood levels. However, no information is available on other neuroactive steroids and the steroidogenic response to hormonal stimulation. For this reason, we evaluated allopregnanolone, pregnanolone, and pregnenolone sulfate by liquid chromatographic procedures coupled with electrospray tandem mass spectrometry in 12 unrelated patients and 15 age‐matched controls. We also tested cortisol, estradiol, progesterone, and 17OH‐progesterone using standard immunoassays. Apart from estradiol and progesterone, all the considered hormones were evaluated in basal condition and after stimulation with adrenocorticotropic hormone (ACTH). A generalized decrease in blood levels of almost all measured neuroactive steroids was found. When considering sexual development, cortisol and pregnenolone sulfate basal levels were significantly reduced in postpubertal girls affected by PCDH19‐FE. Of interest, ACTH administration did not recover pregnenolone sulfate serum levels but restored cortisol to control levels. In prepubertal girls with PCDH19‐FE, by challenging adrenal function with ACTH we disclosed defects in the production of cortisol, pregnenolone sulfate, and 17OH‐progesterone, which were not apparent in basal condition. These findings point to multiple defects in peripheral steroidogenesis associated with and potentially relevant to PCDH19‐FE. Some of these defects could be addressed by stimulating adrenocortical activity.